If ( x + 1 ) 4 + ( x + 3 ) 4 = 4 .Then find the sum of all non-real solutions of the given equation.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Simple standard approach of recognizing that the quartic can be expressed as a quadratic.
Thanks. I've updated the problem accordingly.
Same solution
Identical solution as yours.
Alright , here is my solution , we can see that the equation on the LHS is symmetric about the point x = − 2 , And is strictly increasing from − ∞ to − 3 , then constant from − 3 to − 1 and then again strictly increasing from − 1 to ∞ . Hence the graph of ( x + 1 ) 4 + ( x + 3 ) 4 cuts the line y = 4 only twice , once before − 3 and once after − 1 as it is strictly increasing . Therefore , the two solutions are of the form − 2 + t and − 2 − t ; since symmetry about the point x = − 2 and so , the sum of these two solutions = − 2 − t − 2 + t = − 4
wow , the most unique solution bro . it just removed all those calculations . great idea !!!!
This solution is a little bit longer but i use more complex geometry and i think it's nice.
Let x = a + i b
Now because ( x + 1 ) 4 + ( x + 3 ) 4 = 4 .
It must be that ( x + 1 ) 4 and ( x + 3 ) 4 are real.
So their argument are equal to k π .
4 a r c t a n ( a + 1 b ) = k π
4 a r c t a n ( a + 3 b ) = c π
a + 3 b = t a n ( 4 c π )
a + 1 b = t a n ( 4 k π )
And you will get the equation that says
a = t a n ( 4 k π ) − t a n ( 4 c π ) 3 t a n ( 4 c π ) − t a n ( 4 k π )
The only two cases are for ( t a n ( 4 c π ) , t a n ( 4 k π ) ) = ( 1 , − 1 ) , ( − 1 , 1 ) , others are undefined or real.
So the answer is a 1 = a 2 = − 2
Problem Loading...
Note Loading...
Set Loading...
Put x + 2 = t
The given equation becomes ( t − 1 ) 4 + ( t + 1 ) 4 = 4
t 4 + 6 t 2 + 1 = 2
t 4 + 6 t 2 − 1 = 0
t 2 = 2 − 6 ± 3 6 + 4
Non real complex solutions of the equation are given by t 2 = 2 − 6 − 4 0 (i.e. when t 2 is negative)
( x + 2 ) 2 = − 2 − 6 − 4 0
Sum of roots = − coefficient of x 2 coefficient of x = − 4
NOTE: This is for the question creater. As the real numbers are also complex numbers you should mention "non real complex" in your question.